Species-specific regulatory pathways of small RNAs play sophisticated roles in flower development in Dimocarpus longan Lour. - Bo Liu; Guanliang Li; Chengjie Chen; Zaohai Zeng; Jing Xu; Jisen Zhang; Rui Xia; Yuanlong Liu (Horticultural Plant Journal, 2023)
Flower development plays vital role in horticultural plants. Post-transcriptional regulation via small RNAs is important for plant flower development. To uncover post-transcriptional regulatory networks during the flower development in Dimocarpus longan Lour. ‘Shixia’, an economically important fruit crop in subtropical regions, we collected and analyzed sRNA deep-sequencing datasets and degradome libraries Apart from identifying miRNAs and phased siRNA generating loci (PHAS loci), 120 hairpin loci, producing abundant sRNAs, were identified by in-house protocols. Our results suggested that 56 miRNA-target pairs, 22 21-nt-PHAS loci, and 111 hairpin loci are involved in post-transcriptional gene silencing during longan reproductive development. Lineage-specific or species-specific post-transcriptional regulatory modules have been unveiled, including miR482-PHAS and miRN15. miR482-PHAS might be involved in longan flower development beyond their conserved roles in plant defense, and miRN15 is a novel miRNA likely associated with a hairpin locus (HPL-056) to regulate strigolactone receptor gene DWARF14 (D14) and the biogenesis of phasiRNAs from D14. These small RNAs are enriched in flower buds, suggesting they are likely involved in post-transcriptional regulatory networks essential for longan flower development via the strigolactone signaling pathway.